Analysis of Citizenship Education materials as an effort to strengthening the constitution in perspective character building - Muryati, Sri; Khoirunnisak, Anis (Academy of Education Journal, 2024)
This study aims to describe the analysis of civics education material as an effort to strengthen the constitution in a character education perspective. This type of research is descriptive qualitative. The research subjects were Lecturers and Students of PPKn at the Bangun Nusantara University, Sukoharjo, and the objects: Civics material, constitution and character education. Data collection methods: observation, interviews and documentation. Data validation uses source and material triangulation. Data analysis using interactive analysis techniques. The results of research based on field observations found: constitutional material is limited, lecturers are less able to develop constitutional material, lecturers do not relate constitutional material to actual cases, students are less enthusiastic about participating in lectures, and the presentation of material does not touch the amended constitution. The results of interviews with PPKn lecturers and students obtained information: constitutional material emphasized aspects of knowledge, students did not like rote material, needed a variety of real cases. Conclusion: from the results of observations and interviews it was concluded that it was necessary to update Civics material related to the constitution in a character education perspective.